2020
DOI: 10.4067/s0717-95022020000401018
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Equine Placenta at First Trimester

Abstract: The equine placenta is a simple apposition of fetal and maternal tissues, becoming more complex with the formation of microcotyledons around days 75 and 100 of gestation. The present study aimed to describe the gross and microscopic morphology of early equine placenta. Embryonic/fetal membranes from thirty-seven mares were submitted to macroscopic description, light, scanning and transmission microscopy. Overall the gross characteristics of membranes were similar with already described for older stages. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…AC is the main source of the equine fetal placenta ( Franciolli et al, 2020 ), according to the previous study, its rapid proliferation and increasing interaction with endometrium are promoted by the uterus-derived hepatocyte growth factor-scatter factor (HGF-SF) and epidermal growth factor (EGF) ( Lennard et al, 1998 ; Gerstenberg et al, 1999 ), and in accordance with it, we found AC has high-level expression of EGFR and HGFR. It is known that transforming growth factor-beta (TGF-B) plays an important role in embryo implantation ( Maurya et al, 2013 ), consistently, the TFG-B pathway is significantly enriched in AC.…”
Section: Discussionsupporting
confidence: 54%
“…AC is the main source of the equine fetal placenta ( Franciolli et al, 2020 ), according to the previous study, its rapid proliferation and increasing interaction with endometrium are promoted by the uterus-derived hepatocyte growth factor-scatter factor (HGF-SF) and epidermal growth factor (EGF) ( Lennard et al, 1998 ; Gerstenberg et al, 1999 ), and in accordance with it, we found AC has high-level expression of EGFR and HGFR. It is known that transforming growth factor-beta (TGF-B) plays an important role in embryo implantation ( Maurya et al, 2013 ), consistently, the TFG-B pathway is significantly enriched in AC.…”
Section: Discussionsupporting
confidence: 54%
“…Nonetheless, the placenta reaches full maturity only around day 150 of gestation, and cardiovascular alterations are not described in the first trimester of pregnancy. 49 Consequently, longitudinally following the same group of mares has allowed the identification of significant fluctuations, and T1 values might be considered similar to those of nonpregnant mares.…”
Section: Discussionmentioning
confidence: 99%
“…Another important limitation was the absence of a control group of nonpregnant mares; the study was conducted on Italian Standardbred horse farms, in which most of the animals were pregnant, and there were not enough nonpregnant mares to enroll in the control group. Nonetheless, the placenta reaches full maturity only around day 150 of gestation, and cardiovascular alterations are not described in the first trimester of pregnancy 49 . Consequently, longitudinally following the same group of mares has allowed the identification of significant fluctuations, and T1 values might be considered similar to those of nonpregnant mares.…”
Section: Discussionmentioning
confidence: 99%